Restitution to Victims of Rape Crimes: Examination of Judicial Decision Number 06/JN/2019/MS.Lsm - Djawas, Mursyid; Sumardi, Dedy; Yusdiana, Ratna; Nabila, Atika; Yumna, Cut Najwa Safa (Legitimasi: Jurnal Hukum Pidana dan Politik Hukum, 2024)
Recompense for victims of rape is governed by Article 51 of the Aceh Jinayat Law, which underscores the victim's entitlement to request recompense. In reality, judges do not impose restitution punishments on all rape cases, as the victims of rape do not submit a restitution request. This results from a deficiency in comprehension concerning the procedure for seeking recompense for the victim's incurred losses. This study examines the provision of recompense for rape victims through the lens of Islamic criminal law, specifically concerning the nature and status of reparation. This paper is a normative legal analysis. Data acquisition was performed via library research. The research findings indicate that the restitution mechanism within the Qanun Jinayat is inadequately detailed, resulting in numerous rape victims being unable to seek restitution. Consequently, judges cannot impose restitution penalties without such requests from the victims. In Islamic criminal law, reparation holds an equivalent status to diyat. The method for restitution in Islam does not necessitate a request; instead, the judge explicitly determines that the culprit is obligated to pay diyat to the victim of rape for their crimes. Consequently, the government should establish an institution to provide restitution to rape victims if the perpetrator is unable to pay restitution, as the provision of restitution is contingent upon the financial capability of the perpetrator. Furthermore, standards should be established to determine the minimum reparation that the offender must provide to the rape victim, ensuring that the restitution aligns with the losses incurred by the victim.